Evaluation Of Competitiveness Of The Indonesian Food Manufacturing Industry - Mohammad Amin, Azharuddin (2007)

(untitled)
The development of the Indonesian food manufacturing industry has experienced a rapid growth. Its performance is very encouraging primarily in the aspects of the structural deepening, the diversification and the market orientation. However, the industry has faced an inefficient use of productive resources accumulation, low efficiency and productivity growth as well as small share in the international market. The objective of this study is to evaluate the competitiveness of the Indonesian food manufacturing industry. At the production level, the social profitability indicators such as the Domestic Resource Cost (DRC), the Net Social Profit (NSP) and the Social Cost Benefit (SCB) were applied to estimate the comparative advantage. In measuring efficiency and Total Factor Productivity (TFP) growth, the Data Envelopment Analysis (DEA) and the Malmquist index were used. To assess a market share, the Revealed Comparative Advantage (RCA) and the Relative Trade Advantage (RTA) indicators were employed. The secondary data of inputs-output and trade data in the form of pooled data were collected. The study focused on three different industrial trade policy regimes (imports substitution, exports oriented and emerging and supporting industries). There are 54 sub sectors involved in the comparative advantage analysis, 55 and 42 sub sectors in the efficiency and productivity growth analyses for the total and medium scales and the large scale industries respectively, and 55 sub sectors in the market share analysis. All data are in the form of an international standard industrial classification (ISIC) code at 5 digits. The period of study covered was from 1996 to 2002. Then it was grouped into two sub periods i.e. two years before the economic crisis (1996/1997) and five years after the economic crisis (1998/2002). The result shows that the Indonesian food manufacturing industry has a comparative advantage and is economically efficient in resource allocation, particularly for the import substitution and export oriented industries. However, under the emerging and supporting industry, only the malt liquors and malt sub sector had a comparative disadvantage. In the period of 1996/1997, 14 of the 54 sub sectors had a comparative disadvantage but the situation improved in the period of 1998/2002 where only three sub sectors were comparatively disadvantageous. It suggests that the industry in the subsequent period was economically efficient in the production process and had a declining trend in their production costs. The result of the sensitivity analysis shows that the import substitution industry was very sensitive to the increase in the production costs. Meanwhile, the export oriented and the emerging and supporting industries were sensitive to the decrease in the output border price and the shadow exchange rate appreciation respectively. The most efficient industry was found to be the copra sub sector for the total industry, while for the large and the medium scales, the sub sectors of cooking oil made from palm oil, peeling and cleaning roots and copra were fully efficient. It seems that the import substitution and large scale industries were more efficient throughout the period of analysis. The total industry had positive 9.00 percent of the average annual mean TFP growth rate. For large and medium scale industries, 25 and 15 percent TFP growth rates were respectively achieved. The copra sub sector had the highest positive TFP growth. Overall, the large scale industry performed better than did the medium and total scale industries in TFP growth. The technological change has been the main driving force of TFP growth for all industrial categories. The large scale industry in the period of 1997/1988 was successful in achieving technological mastery. The technological mastery for the total industry was generated from the sub sectors of copra and cooking oil made of coconut oil. In the large scale industry it was contributed by the sub sectors of granular sugar and processing and preserving of fruits and vegetables. In the medium scale industry, it was contributed by the sub sectors of wheat flour, tapioca, granular sugar, sago, bakery products, frozen fish and other similar products, crude palm or vegetable and animal cooking oil, cooking oil made of coconut oil and brown sugar. In market share estimation, under the import substitution industry, all sub sectors had a comparative disadvantage. Under the exports oriented industry, it seems that many food sub sectors were very competitive. However, most of them were intermediate products. Lastly, the sub sectors under the emerging and supporting industry show a decline in their RCA indices in the subsequent period.